Prostate brachytherapy boost: Long-term results of protocol-based treatment of patients with non-metastatic prostate cancer. - Schweizer, Claudia; Strnad, Vratislav; Merten, Ricarda; Schubert, Philipp; Lotter, Michael; Kreppner, Stephan; Fietkau, Rainer; Karius, Andre (Journal of Contemporary Brachytherapy, 2024)
PURPOSE: To evaluate the efficacy and toxicity of interstitial temporary brachytherapy boost for prostate cancer patients using real-world data. MATERIAL AND METHODS: Between 2008 and 2016, 115 patients treated with external beam radiotherapy (EBRT) followed by a brachytherapy boost (BT boost) were eligible for this retrospective analysis. Patients received either interstitial high-dose-rate brachytherapy (HDR-BT) with 2 x 9-9.5 Gray (Gy) schedule or pulsed-dose-rate brachytherapy (PDR-BT) with 35 Gy as boost after EBRT (50.4 Gy), up to a total dose of 86-98 Gy (EQD2α/β = 3). Primary endpoints of the present analysis were cumulative local recurrence rate (LRR), biochemical recurrence-free survival (bRFS), tumor-specific survival, and overall survival (OS). As secondary objective, treatment-related toxicity was evaluated. RESULTS: The median follow-up time was 87 (range, 9-159) months, and the median age was 72 (range, 48-83) years. The median prostate specific antigen value (PSA) was 12.2 (range, 2.4-288) ng/ml. 78/115 (68%) patients had high-risk prostate cancer according to the D'Amico classification. At 7 years, the cumulative LRR for the whole cohort was 1.8%. The 7-year bRFS, cancer-specific survival, and OS were 85.2%, 97.3%, and 88.9%. The 5-year prevalence of late toxicity grade 3 or higher according to the LENT-SOMA scale was 4%. There were no significant differences for treatment outcome or toxicity for HDR vs. PDR treatment. A prostate gland of 50 cm3 or more was not associated with worse treatment efficacy or increased side effects, apart from the prevalence of urethritis after 5 years (p = 0.035). CONCLUSIONS: BT boost in patients with prostate cancer is efficient and well-tolerated, with low rates of side effects also in elderly patients. HDR- and PDR-BT were equally efficient and well-tolerated. A large prostate gland is no contraindication for BT. Therefore, BT boost should be offered to all eligible patients.
EVALuna2:595654